A method for preparing medium-carbon low-chromium ferrochrome using chromium slag
By mixing chromium slag with adhesive to make raw balls, and drying, calcining and smelting, medium-carbon low-chromium ferrochromium products are produced, solving the problems of harmless treatment of chromium slag and low resource reuse efficiency, and achieving efficient resource utilization and economic benefits.
Patent Information
- Application Number
- CN202411988313.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art has problems of efficiency and economic benefits in the harmless treatment of chromium slag and resource reuse, especially in the efficient reduction and conversion of chromium slag.
The medium-carbon low-chromium ferrochromium product is prepared by mixing chromium slag with adhesive to make a ball, and then dried, calcined and smelted, and an intermediate water quenched slag product is obtained by water quenching treatment. This method ensures the strength of raw and cooked balls by adjusting the ratio of chromium slag and adhesive and moisture control, thereby avoiding collapse and powdering during the smelting process, thereby improving resource utilization.
The efficient and harmless treatment of chromium slag and resource reuse have been achieved. The medium-carbon and low-chromium ferrochromium products produced can be used in the steel and wear-resistant casting sphere industries, while the intermediate water-quenching slag products have low chromium content and are suitable for the building materials industry and have good economic benefits.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of comprehensive utilization of chromium slag, and more specifically, relates to a method for preparing medium-carbon low-chromium ferrochrome by utilizing chromium slag. Background Art
[0002] Chromium slag refers to industrial waste residue generated during the production and processing of metallic chromium and chromium salts, metallurgy, electroplating, leather making and other industrial activities. Chromium slag contains toxic substances such as calcium chromate and hexavalent chromium. Chromium slag is generally in powder form and can be easily dissipated in the air. Once lost and spread, it will cause great pollution hazards to the ecological environment and also cause harm to human health.
[0003] At present, there are mainly the following methods for harmless treatment of chromium slag:
[0004] (1) Physicochemical methods
[0005] The physical and chemical method refers to the use of chemical reactions or physical phenomena to transform chromium slag into harmless or recyclable substances. For example, chromium slag can be transformed into a glassy substance by high-temperature melting, thereby achieving the purpose of harmless treatment. In addition, chemical reactions can also be used to transform the chromium in the chromium slag into insoluble chromium compounds. This method does not require the addition of chemical reagents and has little impact on the environment.
[0006] (2) Biological treatment method
[0007] Biological treatment refers to the use of microorganisms to degrade and transform harmful substances in chromium slag. For example, biofilm technology and activated sludge method are used to convert chromium compounds into chromates, and then they are separated by precipitation, adsorption, flotation and other methods. Biological treatment methods have little pollution to the environment, but the treatment efficiency is low and a long treatment cycle is required.
[0008] (3) Hot air drying method
[0009] Hot air drying refers to drying chromium slag with high humidity at high temperature and high humidity to turn it into odorless, dust-free and non-toxic granular material. This method will generate a lot of heat and water vapor during the drying process, which has a certain impact on the environment.
[0010] (4) Solidification treatment method
[0011] Solidification treatment refers to mixing chromium slag with chemical substances to solidify it into a stable solid substance. This method can reduce the volume of chromium slag and reduce its toxicity and harm. However, the balance between the environmental benefits and economic costs of solidification treatment needs to be further studied and discussed.
[0012] (5) Pyrolysis technology
[0013] Pyrolysis technology is a high-temperature decomposition method that heats and decomposes chromium slag in a high-temperature furnace. This method can completely decompose the organic and inorganic substances in the chromium slag and convert them into harmless or recyclable substances. However, due to the need to invest a lot of energy and funds and the high technical difficulty, its current application scope is relatively limited.
[0014] In short, harmless treatment of chromium slag is an environmental issue that urgently needs to be solved. Various treatment methods have their own advantages and disadvantages, and it is necessary to select the appropriate method according to different situations in practical applications. It is now necessary to explore new treatment methods to improve the efficiency and economic benefits of chromium slag treatment. Summary of the invention
[0015] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0016] In order to achieve these objects and other advantages of the present invention, a method for preparing medium-carbon low-chromium ferrochrome using chromium slag is provided, comprising the following steps:
[0017] Step 1: Mix the chromium slag with a binder to form a green ball of a certain diameter;
[0018] Step 2: Dry, calcine and cool the raw balls to obtain cooked balls;
[0019] Step 3, mixing the cooked balls with a reducing agent and a slag-forming agent for smelting to obtain smelted molten iron and smelted slag;
[0020] Step 4: Cast the molten iron after smelting into a mold, cool and demould, and obtain a medium-carbon low-chromium ferrochrome product;
[0021] Step 5: water quench the smelted slag to obtain an intermediate water-quenched slag product.
[0022] Preferably, in step 1, the adhesive is bentonite, and the amount of the adhesive is 1-5% of the mass of the chromium slag.
[0023] Preferably, in the step 1, the water content of the mixture of the chromium slag and the adhesive is controlled to be 15-25% by adding water and drying.
[0024] Preferably, in step 1, the diameter of the green balls is 10 to 30 mm.
[0025] Preferably, in step 1, the strength of the green balls produced is 50 cm drops for more than 10 times.
[0026] Preferably, in step 2, the drying temperature is 100-500° C. and the drying time is 1-3 hours.
[0027] Preferably, in the step 2, the calcination temperature is 1200-1300° C., and the calcination time is 0.5-2 h.
[0028] Preferably, in the step 2, the strength of the cooked ball obtained is greater than 800N.
[0029] Preferably, in step three, the reducing agent is one or more of bituminous coal, coke, and semi-coke.
[0030] Preferably, in step 3, the amount of reducing agent used is 5-15% of the mass of the cooked balls.
[0031] Preferably, in step three, the slag-forming agent is one or both of silica and limestone.
[0032] Preferably, in step 3, the amount of slag-forming agent used is 15-20% of the mass of the cooked balls.
[0033] Preferably, in step three, the smelting temperature is 1550-1850° C., and the smelting time is 1-3 hours.
[0034] Preferably, in the step 4, the medium-carbon low-chromium ferrochrome product obtained is applied to the steel industry and the wear-resistant cast ball industry.
[0035] Preferably, in step five, the intermediate water-quenched slag product obtained is used in the building materials industry.
[0036] Preferably, the step 1 is replaced by: mixing chromium slag, adhesive and additives to form green balls of a certain diameter; wherein the additive addition amount is 1-5% of the mass of the chromium slag.
[0037] Preferably, the preparation method of the auxiliary agent comprises the following steps:
[0038] S1. Mix calcium fluoride and aluminum oxide in a mass ratio of 1-5:1-5, and disperse them in deionized water to obtain a dispersion; wherein the mass volume ratio of the total mass of calcium fluoride and aluminum oxide to deionized water is 1 g:30-100 mL;
[0039] S2. Adding an ethanol solution of hexadecyltrimethoxysilane to the dispersion, stirring at 40-60° C. for 1-3 h, then adding sodium oleate, stirring at 60-80° C. for 2-4 h, centrifuging, washing with anhydrous ethanol and deionized water in sequence, and drying to obtain a powdered product; wherein the concentration of hexadecyltrimethoxysilane in the ethanol solution of hexadecyltrimethoxysilane is 2-6wt%; the mass ratio of the total mass of calcium fluoride and aluminum oxide to that of hexadecyltrimethoxysilane is 1:0.1-0.3; the mass ratio of the total mass of calcium fluoride and aluminum oxide to that of sodium oleate is 1:0.2-0.4;
[0040] S3. The obtained powdered product is kept at 250-350° C. for 20-40 min in an argon atmosphere and naturally cooled to room temperature to obtain an auxiliary agent.
[0041] The present invention at least includes the following beneficial effects: the present invention adjusts the ratio of chromium slag and adhesive, and controls the moisture content, so as to control the strength of green balls (the strength is 50cm drop for more than 10 times), and the purpose of controlling the strength of green balls is to meet the strength requirements of the calcining equipment for the feed pellets, avoid furnace collapse, and reduce pulverization; the strength of cooked balls is effectively controlled (the strength is greater than 800N) by controlling the drying temperature and time, the calcining temperature and time, and the purpose of controlling the strength of cooked balls is to meet the strength requirements of the smelting equipment for the pellets, and avoid furnace collapse; the product is prepared by smelting, and the obtained medium-carbon low-chromium ferrochrome product can be used as a raw material in the steel industry and the wear-resistant cast ball industry, and the obtained intermediate water-quenched slag product has a low chromium content and no hexavalent chromium is detected, and can be directly used in the building materials industry to produce building materials; the present invention has a simple process, realizes the harmless treatment of chromium slag and resource recycling, and has good economic benefits.
[0042] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. DETAILED DESCRIPTION
[0043] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0044] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0045] The main components of the chromium slag used in the following examples are as follows:
[0046] Cr2O3: 6.22%, Fe2O3: 39.54%, Al2O3: 16.10%, SiO2: 11.21%, MgO: 12.43%.
[0047] Example 1
[0048] A method for preparing medium-carbon low-chromium ferrochrome using chromium slag comprises the following steps:
[0049] Step 1: Mix the chromium slag and bentonite, dry them to a moisture content of 25%, and make them into green balls with a diameter of 15 mm. The green ball strength is 50 cm dropped 12 times; wherein the amount of bentonite added is 1% of the mass of the chromium slag;
[0050] Step 2: transport the green balls to a vertical sintering furnace, dry them at 120°C for 4 hours, calcine them at 1200°C for 1 hour, and obtain cooked balls after cooling. The cooked balls have a strength of 820N.
[0051] Step 3: transport the cooked balls to a submerged arc furnace, add coke and silica for smelting at a temperature of 1650°C for 2 hours; wherein the amount of coke added is 8% of the mass of the cooked balls, and the amount of silica added is 16% of the mass of the cooked balls;
[0052] Step 4: After smelting, the molten iron enters the ladle and is cast into a casting machine with a mold size of 150*150*100mm. After cooling and demolding, a medium-carbon low-chromium ferrochrome product is obtained, with a Cr content of 10.77%, a Fe content of 85.16%, and a C content of 3.425%;
[0053] Step 5: The smelted slag is water quenched to obtain an intermediate water-quenched slag product, the main components of which are: Cr2O3: 3.67%, hexavalent chromium is not measured, Fe2O3: 3.62%, AL2O3: 25.64%, SiO2: 29.69%, CaO: 2.55%, and MgO: 20.98%.
[0054] In this embodiment, the comprehensive resource utilization rate of chromium slag is 95.8%.
[0055] Example 2
[0056] A method for preparing medium-carbon low-chromium ferrochrome using chromium slag comprises the following steps:
[0057] Step 1: Mix the chromium slag and bentonite, dry them to a moisture content of 20%, and make them into green balls with a diameter of 15 mm. The green ball strength is 50 cm dropped 14 times; wherein the amount of bentonite added is 2% of the mass of the chromium slag;
[0058] Step 2: transport the green balls to a vertical sintering furnace, dry them at 200°C for 2.5 hours, calcine them at 1250°C for 1 hour, and obtain cooked balls after cooling. The cooked balls have a strength of 870N.
[0059] Step 3: transport the cooked balls to a submerged arc furnace, add coke and silica for smelting at a temperature of 1650°C for 2 hours; wherein the amount of coke added is 10% of the mass of the cooked balls, and the amount of silica added is 18% of the mass of the cooked balls;
[0060] Step 4: After smelting, the molten iron enters the ladle and is cast into a casting machine with a mold size of 150*150*100mm. After cooling and demolding, a medium-carbon low-chromium ferrochrome product is obtained, with a Cr content of 11.22%, a Fe content of 84.27%, and a C content of 3.582%;
[0061] Step 5: The smelted slag is water quenched to obtain an intermediate water-quenched slag product, the main components of which are: Cr2O3: 3.43%, hexavalent chromium is not measured, Fe2O3: 3.25%, AL2O3: 24.58%, SiO2: 28.64%, CaO: 2.35%, and MgO: 21.56%.
[0062] In this embodiment, the comprehensive resource utilization rate of chromium slag is 97.0%.
[0063] Example 3
[0064] A method for preparing medium-carbon low-chromium ferrochrome using chromium slag comprises the following steps:
[0065] Step 1: Mix the chromium slag and bentonite, dry them to a moisture content of 15%, and make green balls with a diameter of 15 mm. The green ball strength is 50 cm dropped 15 times; wherein the amount of bentonite added is 3% of the mass of the chromium slag;
[0066] Step 2: transport the green balls to a vertical sintering furnace, dry them at 250°C for 2 hours, calcine them at 1300°C for 1 hour, and obtain cooked balls after cooling. The strength of the cooked balls is 1050N.
[0067] Step 3: transport the cooked balls to a submerged arc furnace, add coke and silica for smelting at a temperature of 1650°C for 2 hours; wherein the amount of coke added is 12% of the mass of the cooked balls, and the amount of silica added is 20% of the mass of the cooked balls;
[0068] Step 4: After smelting, the molten iron enters the ladle and is cast into a casting machine with a mold size of 150*150*100mm. After cooling and demolding, a medium-carbon low-chromium ferrochrome product is obtained, with a Cr content of 11.31%, a Fe content of 84.14%, and a C content of 3.248%;
[0069] Step 5: The smelted slag is water quenched to obtain an intermediate water-quenched slag product, the main components of which are: Cr2O3: 2.85%, hexavalent chromium not detected, Fe2O3: 2.96%, AL2O3: 27.38%, SiO2: 30.25%, CaO: 2.58%, and MgO: 22.45%.
[0070] In this embodiment, the comprehensive resource utilization rate of chromium slag is 96.5%.
[0071] Example 4
[0072] This embodiment provides a method for preparing medium-carbon low-chromium ferrochrome using chromium slag, which is different from the embodiment 2 only in that: in step 1, when preparing green balls, an additive is added to the mixture of bentonite and chromium slag, and the amount of the additive added is 3% of the mass of the chromium slag; the remaining steps are the same as those in embodiment 2. The preparation method of the additive includes the following steps:
[0073] S1. Mix calcium fluoride and aluminum oxide in a mass ratio of 1:1, and disperse them in deionized water to obtain a dispersion; wherein the mass volume ratio of the total mass of calcium fluoride and aluminum oxide to deionized water is 1 g:50 mL;
[0074] S2. Adding an ethanol solution of hexadecyltrimethoxysilane to the dispersion, stirring at 50° C. for 2 h, then adding sodium oleate, stirring at 70° C. for 3 h, centrifuging, washing with anhydrous ethanol and deionized water in sequence, and drying to obtain a powdery product; wherein the concentration of hexadecyltrimethoxysilane in the ethanol solution of hexadecyltrimethoxysilane is 5wt%; the mass ratio of the total mass of calcium fluoride and aluminum oxide to that of hexadecyltrimethoxysilane is 1:0.2; the mass ratio of the total mass of calcium fluoride and aluminum oxide to that of sodium oleate is 1:0.3;
[0075] S3. The obtained powdered product is kept at 300° C. for 30 min in an argon atmosphere and naturally cooled to room temperature to obtain an auxiliary agent.
[0076] In this embodiment, aluminum oxide and calcium fluoride are used as raw materials, and hexadecyltrimethoxysilane and sodium oleate are used for modification to prepare an additive. The additive has good dispersibility and can be evenly distributed in the green balls. At the same time, it has a good slag-making and fluxing effect. It is mixed with chromium slag and bentonite to prepare green balls, which is beneficial to more complete reduction of the chromium slag in the subsequent reaction process and further improves the comprehensive resource utilization rate of the chromium slag. The comprehensive resource utilization rate of the chromium slag in Example 4 is 98.1%.
[0077] Example 5
[0078] This embodiment provides a method for preparing medium-carbon low-chromium ferrochrome using chromium slag, which is different from Embodiment 2 only in that: in step 1, when preparing green balls, aluminum oxide and calcium fluoride are added to the mixture of bentonite and chromium slag, the mass ratio of aluminum oxide to calcium fluoride is 1:1, and the total amount of aluminum oxide and calcium fluoride added is 3% of the mass of the chromium slag; the remaining steps are the same as those in Embodiment 2. In this embodiment, the comprehensive resource utilization rate of the chromium slag is 97.3%.
[0079] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the embodiments shown and described herein.
Claims
1. A method for preparing medium-carbon low-chromium ferrochrome using chromium slag, characterized in that: The following steps are involved: Step 1: Mix the chromium slag with a binder to form a green ball of a certain diameter; Step 2: Dry, calcine and cool the raw balls to obtain cooked balls; Step 3, mixing the cooked balls with a reducing agent and a slag-forming agent for smelting to obtain smelted molten iron and smelted slag; Step 4: Cast the molten iron after smelting into a mold, cool and demould, and obtain a medium-carbon low-chromium ferrochrome product; Step 5: water quench the smelted slag to obtain an intermediate water-quenched slag product.
2. The method for preparing medium-carbon low-chromium ferrochrome using chromium slag as claimed in claim 1, characterized in that: In the step 1, the adhesive is bentonite, and the amount of the adhesive is 1-5% of the mass of the chromium slag.
3. The method for preparing medium-carbon low-chromium ferrochrome using chromium slag according to claim 1, characterized in that: In the step 1, the water content of the mixture of chromium slag and adhesive is controlled at 15-25%; the diameter of the green ball is 10-30 mm.
4. The method for preparing medium-carbon low-chromium ferrochrome using chromium slag as claimed in claim 1, characterized in that: In the step 2, the drying temperature is 100-500° C., and the drying time is 1-3 hours.
5. The method for preparing medium-carbon low-chromium ferrochrome using chromium slag according to claim 1, characterized in that: In the step 2, the calcination temperature is 1200-1300° C., and the calcination time is 0.5-2 hours.
6. The method for preparing medium-carbon low-chromium ferrochrome using chromium slag according to claim 1, characterized in that: In the step three, the reducing agent is one or more of bituminous coal, coke, and semi-coke.
7. The method for preparing medium-carbon low-chromium ferrochrome using chromium slag according to claim 1, characterized in that: In the step 3, the amount of reducing agent used is 5-15% of the mass of the cooked balls.
8. The method for preparing medium-carbon low-chromium ferrochrome using chromium slag as claimed in claim 1, characterized in that: In the step 3, the slag-forming agent is one or both of silica and limestone.
9. The method for preparing medium-carbon low-chromium ferrochrome using chromium slag as claimed in claim 1, characterized in that: In the step 3, the amount of slag-forming agent used is 15-20% of the mass of the cooked balls.
10. The method for preparing medium-carbon low-chromium ferrochrome using chromium slag according to claim 1, characterized in that: In the step 3, the smelting temperature is 1550-1850° C., and the smelting time is 1-3 hours.